Li-doped transition metal high-entropy oxides (Li/TM-HEOs) as Li-Ion batteries cathodes: a first report on capacity fading and cycling stability - Luca Spiridigliozzi; Andrea Filippo Di Feo; Grazia Accardo; Uxue Gonzalez Mendizabal; Emanuele De Bona; Gianfranco Dell’Agli (Materials Research Express)
High-Entropy Oxides (HEOs) have gained significant attention for their wide range of compositions and potential applications across various sectors, including rechargeable batteries. This study explores the characterization of two distinct HEO systems as potential cathode materials for Lithium-ion batteries (LIBs). A series of rock salt structured HEOs with varying Li loadings (16Li/RS-HEO, 25Li/RS-HEO, 33Li/RS-HEO, and 41Li/RS-HEO) and a spinel-structured HEO with 16 mol% of Li loading (16Li/SP-HEO) were firstly synthesized through co-precipitation. Electrochemical analyses via cyclic voltammetry revealed stark differences in the behavior of these structures. The Li/SP-HEO sample displayed broad and strongly irreversible hysteresis cycles, while the Li/RS-HEO series manifested thin, narrow hysteresis cycles with single oxidation peaks between 0.5 V and 0.7 V. As the lithium content increases in the RS-HEO system, the cycling stability of the cell decreases, most likely due to the reduced ratio of transition metal cations to lithium ions. Although there was a noticeable decrease in capacity under higher current rates, the higher lithium loadings positively impact the cell capacity, albeit with notable capacity fading under higher current rates. Li-doped rock salt structured high entropy materials show potential for LIB cathodes in terms of high specific capacities; the observed stability issues at medium and high current densities indicate a rapid electrode degradation.